Teacher's Effective Strategy in Overcoming Student Learning Saturation - Amini, Izzat; Rofilah, Rofilah (Universitas Al-Amien Prenduan, 2023)
Saturation of learning is a phenomenon that often occurs in schools. The main cause of learning saturation is caused by student and teacher factors. This study aims to determine the factors that cause student learning saturation and teachers' effective strategies in dealing with learning saturation. This research is a qualitative research with a case study approach. The results of this study indicate that the factors causing learning saturation are the lack of variation in learning, the lack of student motivation in learning. The strategies that can be used by teachers are setting clear and futuristic goals, compiling a structured learning design, creating a conducive learning environment, accommodating varied learning strategies, and conducting appropriate and measurable learning evaluations.